2015
DOI: 10.1530/joe-15-0131
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the hypothalamus and gut to weight gain susceptibility and resistance in mice

Abstract: Obesity susceptibility in humans and in rodent strains varies in response to the consumption of high-energy density (HED) diets. However, the exact mechanism(s) involved in this susceptibility remain(s) unresolved. The aim of the present study was to gain greater insight into this susceptibility by using C57BL/6J (B6) mice that were separated into obesity-prone (diet-induced obese (DIO)) and obesity-resistant (diet-induced resistant (DR)) groups following an HED diet for 6 weeks. Physiological, biochemical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…Most notably, FFA4 expression was upregulated in diet-induced obesity (DIO) rat models, 316,317 while it was downregulated in C57Bl6 mouse DIO models. 318 In studies measuring expression of FFA4 mRNA in human duodenum, a direct correlation was observed between body mass index and FFA4 transcript levels, 319 seeming to match well with the observations in DIO rats. Interestingly, FFA4 expression levels in cultured Caco-2 intestinal epithelial cells appear to be regulated by different species of gut microbiota, perhaps suggesting that FFA4 may have an indirect role in linking gut microbiota to health.…”
Section: Expression Of Ffa4supporting
confidence: 59%
See 1 more Smart Citation
“…Most notably, FFA4 expression was upregulated in diet-induced obesity (DIO) rat models, 316,317 while it was downregulated in C57Bl6 mouse DIO models. 318 In studies measuring expression of FFA4 mRNA in human duodenum, a direct correlation was observed between body mass index and FFA4 transcript levels, 319 seeming to match well with the observations in DIO rats. Interestingly, FFA4 expression levels in cultured Caco-2 intestinal epithelial cells appear to be regulated by different species of gut microbiota, perhaps suggesting that FFA4 may have an indirect role in linking gut microbiota to health.…”
Section: Expression Of Ffa4supporting
confidence: 59%
“…Interestingly, several factors seem to regulate FFA4 expression in the intestine, and these may be species and/or strain dependent. Most notably, FFA4 expression was upregulated in diet-induced obesity (DIO) rat models, , while it was downregulated in C57Bl6 mouse DIO models . In studies measuring expression of FFA4 mRNA in human duodenum, a direct correlation was observed between body mass index and FFA4 transcript levels, seeming to match well with the observations in DIO rats.…”
Section: Ffa4mentioning
confidence: 99%
“…The expression of SSTr1-5 was investigated using custom-designed 384-well quantitative PCR plates from Lonza, Denmark. Data are shown as expression relative to a mean of three housekeeping genes, 18S ribosomal RNA, tyrosine 3-monooxygenase/tryptophan 5-monooxygenase activation protein (YWHAZ), and hypoxanthine phosphoribosyltransferase 1 (HPRT1) (15,55), and calculated using the Livak method (34). The sequences used for the five receptors and the housekeeping genes are listed in Supplemental Table S2 (https://doi.org/10.6084/m9.figshare.8307386) and published in Ref.…”
Section: Methodsmentioning
confidence: 99%
“…Food intake and voluntary physical activity were measured at 12 weeks of age and fasting energy expenditure was measured at 6 and 12 weeks of age as previously described (Cui et al 2015, Fam et al 2015. Briefly, food intake was determined in mice that were housed separately by weighing food each morning over a seven-day period and daily food intake averaged over the seven days.…”
Section: Metabolic Analysesmentioning
confidence: 99%
“…Briefly, food intake was determined in mice that were housed separately by weighing food each morning over a seven-day period and daily food intake averaged over the seven days. Voluntary activity was measured by monitoring the use of running wheels with a computerised metre (Fam et al 2015) and fasting energy expenditure was determined by measuring the body weight of the mice prior to and following an overnight fast of 16 h and calculated as the change in body weight (Cui et al 2015).…”
Section: Metabolic Analysesmentioning
confidence: 99%